The problem of death: a challenge for nursing students - Charalambous, Andreas (My University, 2002)
The process of death and dying consists one of the major challenges that health workers face during their professional carrier. In Cyprus, the dynamic of the problem presents special features since the problem still is been considered as a taboo topic. These parameters of the problem have shaped in my mind the need to address this situation in order to seek out and find the best possible solutions. The primary goal of this essay is to investigate and study all the relative information concerning the dying patient and death in general. Special attention is given to those situations where the student nurse is delivering the care. However, the focus of this paper is not on the dying patient, but on the problems the students face in introducing a holistic approach to death and dying. These parameters are analyzed in relation to the nursing program of change, the nursing educators and clinical tutors and finally the nursing professionals in the different units. Persona/ experience is used along with the experience of other professional so that the process is supported. Α bibliographical support to the process is also been used in order to achieve results that are substantial evidenced. /n the last part, the results of this work are presented to the reader along with the relative bibliography offering this way a broader angle to the problem.
Keywords: Death; Health workers; Nurses